2015
DOI: 10.1080/01457632.2015.972726
|View full text |Cite
|
Sign up to set email alerts
|

Flow Boiling Phenomenological Differences Between Micro- and Macroscale Channels

Abstract: In this paper flow boiling phenomenological differences between micro and macroscale channels are discussed. Analyses of flow pattern results are performed in order to identify the main differences between micro-and macro-scale phenomena. Based on these analyses important flow pattern differences between micro and macro-scale behaviors were identified, and new phenomenological transition criteria based on flow patterns are presented. These criteria are based on the existence of stratified flow and on the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Thus, the uniform film thickness criterion proposed by Tibirica and Ribatski [23] matches the microchannel criterion of Cheng and Wu [16].…”
Section: Figure 3: Large Variation In the Convective Confinement Numbmentioning
confidence: 53%
See 2 more Smart Citations
“…Thus, the uniform film thickness criterion proposed by Tibirica and Ribatski [23] matches the microchannel criterion of Cheng and Wu [16].…”
Section: Figure 3: Large Variation In the Convective Confinement Numbmentioning
confidence: 53%
“…In 2015, Tibirica and Ribatski [23], by combining a broad literature review with their own experiments using tubes with diameters from 1.00 to 2.32 mm, concluded that the key characteristics of microscale tubes are (1) the absence of stratified flows and (2) uniformity of the liquid film thickness along the tube perimeter for slug and annular flows in horizontal channels. Using an analytical model, they determined the maximum diameter for which a liquid slug could exist in a tube under static conditions was…”
Section: Figure 3: Large Variation In the Convective Confinement Numbmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 reveals a certain degree of nonuniformity of the liquid film along the tube perimeter. Recently, this aspect was taken into account to characterize micro-and macro-scale behaviors by Ong and Thome [22], Tibiriçá [31] and Tibiriça and Ribastki [32]. Based on flow pattern behaviors and on the degree of uniformity of the liquid film along the tube perimeter, Ong and Thome [22] developed a new macro-to-micro-scale threshold criterion; moreover, they included a transitional region between them.…”
Section: Subjective Characterizationmentioning
confidence: 99%
“…According to the Ong and Thome [22] criterion, the two-phase flow results obtained in the present study are within the mesoscale range. More recently, Tibiriçá [31] and Tibiriça and Ribastki [32] developed two macro-to micro-threshold criteria, based on the degree of uniformity of the film along the tube perimeter and the capillary height, considered as criterion for the occurrence of stratified flows. According to both criteria proposed by them, the results for a 2.32-mm ID tube are characterized as macroscale two-phase flows while for a 1.1-mm ID tube are microscale two-phase flows.…”
Section: Subjective Characterizationmentioning
confidence: 99%